Assessment of Water Quality in the Stream Flows into the Krasiow Dam based on Hydropsychid Larvae (Insecta, Trichoptera) - Choeychom, Suriyaporn; On Prommi, Taeng (Journal of Food Health and Bioenvironmental Science, 2023)
The use of altered gill morphology in hydropsychid larvae (Hydropsychidae: Trichoptera) as water quality biomonitoring was conducted in streams flows into Krasiow Dam, Dan Chang district, Suphan Buri Province, Thailand. Samples were collected over a period of one year January to December 2019. In total, 5,583 individual hydropsychid larvae belonging to four genera (Amphipsyche meridiana, Macrostemum indistinctum, Cheumatopsyche spp. and Potamyia spp.) were identified in this study. The percentage of individuals with at least some abnormality (HAI) and hydropsychid gill abnormality indice (HYI) was the highest in February and lowest in October. Canonical Correspondence Analysis (CCA) indicated the species Amphipsyche meridiana were positively correlated with water temperature, pH, and ammonia-nitrogen. Total dissolved solids were negatively associated with the Cheumatopsyche spp. and Macrostemum indistinctum. The outcomes of this study is expected that analyses of morphological deformations in tracheal gills could become a support for traditional physicochemical analyses of water quality or traditional biomonitoring.